Complex Pediatric Neuroblastoma Presenting With Superior Vena Cava Syndrome, Tumor Lysis, and Massive Pleural Effusion - Maya Novariza; Sri Mulatsih, MD, PhD; Pudjo Hagung Widjajanto; Alexandra Pangarso; Dito Pondra Dharma; Aulia Suluk Brilliant Sumpono; Yunanto Kurnia; Clements Nicodhemus Garuda Nagara (Indonesian Journal of Cancer, 2026)
Background: The simultaneous presence of superior vena cava syndrome, tumor lysis syndrome, massive pleural effusion, and metabolic syndrome in a child with mediastinal neuroblastoma is exceedingly rare and sparsely described in the literature. The concurrent occurrence of superior vena cava syndrome (SVCS), tumor lysis syndrome (TLS), massive pleural effusion, and metabolic syndrome in a pediatric patient is exceedingly rare and poses significant diagnostic and therapeutic challenges. This case report highlights a rare and urgent clinical scenario involving these overlapping conditions.Case Presentation: An 8-year-old girl presented with shortness of breath, facial swelling, cough, and a neck lump. Imaging revealed a large mediastinal mass with massive right pleural effusion. Laboratory findings supported the diagnosis of TLS and metabolic syndrome in the context of obesity. Histopathology confirmed the differentiation of neuroblastoma. The patient was managed with steroids, chemotherapy, drainage, and supportive care, including metabolic syndrome assessment and nutritional interventions. Conclusions: This case emphasizes the importance of early recognition and multidisciplinary management of complex pediatric oncology emergencies. SVCS, TLS, and massive pleural effusion may co-occur in rare mediastinal neuroblastomas, especially in children with obesity and metabolic syndrome. Prompt recognition and integrated multidisciplinary care are essential to improve outcomes in complex pediatric oncology emergencies.